Musical and socio-cultural anecdotes from Kitab al-aghani al-kabir - Sawa, George, 1947- (Islamic History and Civilization, 2018)
The present volume consists of translated anecdotes, on musicological and socio-cultural topics, from al-Iṣbahānī's Kitāb al-Aghānī al-Kabīr ( The Grand Book of Songs ) with annotations and commentaries. It deals with musical rhythmic and melodic modes, technical terms and treatises; music instruments; composition techniques and processes; education and oral/written transmissions; vocal and instrumental performances and their aesthetics; solo and ensemble music; change and its inevitability; musical and textual improvisations; ṭarab and the acute emotions of joy or grief; medieval dances; social status. Though extracts from The Grand Book of Songs have been translated in European languages since 1816, this work presents a much larger and more comprehensive scope that will benefit musicologists, medievalist and Middle Eastern scholars as well as the general reader.